Laser Synthesis of Nanometric Chromium Oxide Films with High Seebeck Coefficient and High Thermoelectric Figure of Merit: An Experimental Study - N. Stefan; S. A. Mulenko; N. T. Gorbachuk (Current Overview on Science and Technology Research Vol. 4, 2022)
The synthesis of nanometric chromium oxide films with variable thickness, stoichiometry, and electrical characteristics was carried out using ultraviolet photons from a KrF- laser (\(λ\) = 248 nm).Reactive pulsed laser deposition (RPLD) served as the basis for the synthesis (RPLD). On a <100>Si substrate, film deposition was done between 293 and 800 K. Films placed on a Si substrate have polycrystalline structure, according to XRD measurements. Depending on the substrate temperature, oxygen pressure in the reactor, and film thickness, all films displayed semiconductor temperature behaviour with changeable band gap (Eg) smaller than 1.0 eV. The relationship between film thickness (55-200) nm and oxygen pressure, substrate temperature, and laser pulse frequency was studied. It was found out that the optimum thermo electromotive force coefficient (Seebeck coefficient, S) was high as (3.0-8.0) mV/K and the thermoelectric figure of merit (ZT) was high as 0.23-5.0 in the range of (280-330) K. This made Cr3-XO3-Y nanometric films, which were created using the RPLD process based on UV photons, an incredibly strong contender for efficient thermo-sensors and thermo-converters operating at moderate temperatures. Therefore, the main objective of the investigations submitted in this paper is to establish of conditions for increasing thermoelectric properties of nanometric chromium oxide films.